IMPLEMENTASI INTERACTIVE SMARTBOARD UNTUK MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPAS - Ridho Hendrawan; Masrurotul Mahmudah; Lutfi Fadilah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the application of the Interactive Smartboard as an interactive learning medium in increasing students' learning interest in science learning for fifth-grade students at SD NU Metro. This research uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart model, carried out in two cycles involving 29 students. Data collection techniques were conducted through questionnaires, observations, and interviews, while data analysis used a quantitative descriptive approach. The results of the study showed an increase in the completeness of students' learning interest after the application of the Interactive Smartboard. In the pre-cycle, students who reached completeness were 9 students (31.03%), increasing in Cycle I to 18 students (62.07%), and in Cycle II increased to 25 students (86.21%), thus meeting the established success indicators. In addition, the results of observations showed an increase in student involvement and active participation in the learning process Thus, it can be concluded that the use of Interactive Smart Boards can create learning that is more interactive, engaging, and meaningful, thereby being effective in increasing students' interest in learning Natural and Social Sciences in elementary schools. ABSTRAK Penelitian ini bertujuan untuk menganalisis penerapan Interactive Smartboard sebagai media pembelajaran interaktif dalam meningkatkan minat belajar siswa pada pembelajaran IPAS pada siswa kelas V SD NU Metro. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus dengan melibatkan 29 siswa. Teknik pengumpulan data dilakukan melalui angket, observasi, dan wawancara, sedangkan analisis data menggunakan pendekatan deskriptif kuantitatif. Hasil penelitian menunjukkan adanya peningkatan ketuntasan minat belajar siswa setelah penerapan Interactive Smartboard. Pada pra-siklus, siswa yang mencapai ketuntasan sebanyak 9 siswa (31,03%), meningkat pada Siklus I menjadi 18 siswa (62,07%), dan pada Siklus II meningkat menjadi 25 siswa (86,21%), sehingga telah memenuhi indikator keberhasilan yang ditetapkan. Selain itu, hasil observasi menunjukkan peningkatan keterlibatan dan partisipasi aktif siswa dalam proses pembelajaran. Dengan demikian, dapat disimpulkan bahwa penggunaan Interactive Smartboard mampu menciptakan pembelajaran yang lebih interaktif, menarik, dan bermakna sehingga efektif dalam meningkatkan minat belajar siswa pada pembelajaran IPAS di sekolah dasar.